2001
DOI: 10.1021/jp011783t
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Barriers To Conformational Interchange in Oligothiophenes and Oligo(Thienyl)furans

Abstract: The conformational analysis of unsubstituted and alkyl-substituted oligothiophenes and oligo(thienyl)furans by dynamic NMR (DNMR) spectroscopy and ab initio calculations is described. The DNMR studies of oligothiophenes indicate that the conformational exchange is fast even on the 13 C chemical shift scale and that the barriers are too low to be measured by this technique. Ab initio 6-31G** and MP2/6-31G** calculations are in agreement with these experimental findings. Moreover, it is found that the torsional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 61 publications
8
45
0
Order By: Relevance
“…The comparison of the calculated structures with experimental X-ray data as well as gas-phase and solution conformational studies has also been carried out (see Diaz-Quijada et al (2002) for review). Most of these studies have concentrated on the rotational barrier and its impact on the spectroscopic and photophysical properties of oligothiophenes.…”
Section: (B ) Geometrymentioning
confidence: 99%
“…The comparison of the calculated structures with experimental X-ray data as well as gas-phase and solution conformational studies has also been carried out (see Diaz-Quijada et al (2002) for review). Most of these studies have concentrated on the rotational barrier and its impact on the spectroscopic and photophysical properties of oligothiophenes.…”
Section: (B ) Geometrymentioning
confidence: 99%
“…There are no known data on the gasphase geometry of alkylated oligothiophenes. The closest match is a dynamic NMR study which found that alkylated dimers interconverted rapidly between syn-like and anti-like forms even at 140 K, and thus inferred that the barrier between configurations is very low [41]. Ab initio studies at levels of theory ranging from HF/3-21G* to HF/6-31G** also suggest a low barrier to ring rotation in oligo(alkylthiophenes), and that the addition of side chains should favor a geometry that is further deplanarized compared to plain oligothiophene [45,59,43].…”
Section: Geometry and Partial Chargesmentioning
confidence: 91%
“…Perhaps the most important reason is that existing AMBER force fields were parameterized at this level of theory [38], and consistency with the existing parameters is a primary goal of our work. However, another deciding factor is that HF/6-31G* optimizations and rotations have been shown by other investigators to match well with experimental results [39], and the use of higher levels of theory (e.g., MP2) does not substantially change the relative energies of different conformations [40,41].…”
Section: Geometry and Partial Chargesmentioning
confidence: 98%
“…15,[19][20][21] However, the transferability of force-field parameter sets derived from small and simple model molecules to polymers with complex chemical architectures, as for instance PT-c4as, is not always accurate enough. Thus, PT-c4as typically present an alternated distribution of flexible and rigid dihedral angles in the backbone because each calix [4]arene macrocycle connects two adjacent thiophene rings.…”
Section: Introductionmentioning
confidence: 99%